Pó de cajá (Spondia mombin l.) atomizado: caracterização físicas, físico-químicas, sensoriais e avaliação do comportamento higroscópico - Moura Neto, Luis Gomes de (2011)
The hog plum is a fruit that has good physical-chemical and sensory properties, which give it great acceptance by consumers and industry, and presents excellent nutritional quality. It has sugars, vitamin A and C. In this context, this study aimed to apply the process of atomization in hog plum pulp, using two experimental designs, analyzing the process variables on the yield and quality of the product powder. Following the studies of the powders obtained before their physical characteristics, physical-chemical, hygroscopic, and sensory acceptance of a drink (cajá tropical reconstitutedjuice). After acquiring the pulp, it was taken to the laboratory Quality Control and Drying of the DTA / CCA / UFC Fortaleza, where they were stored under refrigeration until the beginning of the process of getting the dust. We used two experimental designs: maltodextrin and / or lecithin as an adjuvant agent. After obtaining parse the parameters of moisture, pH, soluble solids, SS / TA, titratable acidity, total and reducing sugars and colorimetric analysis. Regarding the post, who had maltodextrin and lecithin in the composition stood out from the others in most determinations of physical and physicochemical and sensory attributes, was not only obtained good reputation in the attribute flavor. Among the mathematical models used for the adjustment of adsorption isotherms, the BET model adjusted better to the experimental data of maltodextrin powders with less error and higher correlation coefficient. For the powder with maltodextrin, lecithin, Henderson presented the model is more adjusted, except at a temperature of 40 ° C, than the oneusing the Oswin model. Thus, one can conclude that the application of lecithin in the process of obtaining caja atomized powder is favorable, given the prominence of the post with lecithin in its chemical composition and physical need to study to improve the taste attribute. The spray-dryer process is a good alternative to enjoy the surplus in the production of caja.